Biosimilars - Feijó Azevedo, Valderilio; Moots, Robert (IntechOpen, 2022)
Introduced in the 1980s, biologic medications have since become important tools in modern medicine. However, biologics are expensive, greatly affecting the healthcare budgets of both underdeveloped and developed countries. Fortunately, biosimilars, which are highly similar, reverse-engineered versions of existing biological medicines and their active ingredients, are now available as more affordable options for patients treated with biologics. This book discusses biosimilars with chapters on clinical trials, regulation, pharmacovigilance, and the interchangeability of biosimilars with biologics. It also addresses future trends in the biosimilars market.